Work and Job Related Factors and Job Turnover in Private Universities in Kenya - Kalei, Anne; Wambugu, Hannah Wanjiku (International Journal of Social Science and Economic Research, 2018)
Employee retention in training institutions has become challenging due to a multiplicity of factors. Most studies have has been concentrating on job related causes of labor turnover in government owned training institutions. This study investigated the effect of both job related factors and worker related factors. A sample of 395 employees in public universities was used and the study employed descriptive survey research design and questionnaires were used to collect data. Data was analyzed qualitatively and quantitatively. The results indicated that career progression and the study established that the desire to grow individual careers did lead to workers leaving their jobs in private universities and the effect was significant (Coef= -0.583, P- value=0.002). The study also established that the effect of lack job security was significant (Coef= -0.998, P-value=0.003). The effect of both remuneration and work life balance was also significant (Coef= -0.401, P-value=0.001) and (Coef= -0.398, P-value=0.001) respectively. Worker related factors- age, gender and education had significance effect (Coef= -0.321, P- value=0.003), (Coef= -0.386, P-value=0.001) and (Coef= -0.477, P-value=0.003) respectively. In order to reduce the rate of job turn-over, this study recommends that management of private universities should put in place good work policies touching on career progression, life balancing measures and remuneration. Details in this policy should also guarantee some job security to their workers. The findings are important to the planners in universities in Kenya, if they were ready to have satisfied workers who can remain there for long durations thus ensuring continuity of the institutions.
Keywords: Career progression; Work-life balance; Job security; Remuneration